DEVELOPMENT OF EMPLOYABILITY SKILLS IN THE ERA OF GLOBALIZATION IN THE UNIVERSITY - Kapraja Sangadji; Lorimase Sangadji (Peneliti.net, 2020)
The work challenges in the globalization era are getting heavier so that the workforce is required to have other abilities beyond academic ability. The biggest problem is many high school graduates who are not employed. This is because low non academic ability of college as a trigger. Its mean that non academic ability be a determine factor must be notice in the universities so that the graduates can be take a participation in era of globalization. These non academic abilities includes interpersonal skills, computer skills, enterprise & entrepreneurial skills, communication skills, thinking skills and management skills. Universities as producers of educated young workers must align their curriculum with these non-academic needs in each of their learning activities. There are a number of approaches that can be taken by universities to develop employability skills, including work-integrated learning, stand-alone subject models, academic support programs, embedded subject models, non-academic support programs and campus life activities. the potential of every college graduate can compete in the era of globalization.